Plant Proteomics - Herman, Gerald (Raj Publication, 2018)
A sharp decline in the availability of arable land and sufficient supply of irrigation water along with a continuous steep increase in food demands have exerted a pressure on farmers to produce more with fewer resources. A viable solution to release this pressure is to speed up the plant breeding process by employing biotechnology in breeding programmes. The majority of biotechnological applications rely on information generated from various -omic technologies. The latest outstanding improvements in proteomic platforms and many other but related advances in plant biotechnology techniques offer various new ways to encourage the usage of these technologies by plant scientists for crop improvement programmes. The aim of this book is to give up-to-date methods and protocols used by recognized scientists in the world of plant proteomics. This book is a valuable resource for a broad spectrum of readers ranging from teachers and advanced students to researchers.
Keywords: Proteomics; Plant biology